Page Composition using PPML as a Link-editing Script - Bagley, Steven R.; Brailsford, David F. (ACM Press, 2004)
The advantages of a COG (Component Object Graphic) approach to the composition of PDF pages have been set out in a previous paper [1]. However, if pages are to be composed in this way then the individual graphic objects must have known bounding boxes and must be correctly placed on the page in a process that resembles the link editing of a multi-module computer program. Ideally the linker should be able to utilize all declared resource information attached to each COG. We have investigated the use of an XML application called Personalized Print Markup Language (PPML) to control the link editing process for PDF COGs. Our experiments, though successful, have shown up the shortcomings of PPML's resource handling capabilities which are currently active at the document and page levels but which cannot be elegantly applied to individual graphic objects at a sub-page level. Proposals are put forward for modifications to PPML that would make easier any COG-based approach to page composition.